Meaning of Life Anak Pengidap Kanker serta Peran Bimbingan dan Konseling Komunitas - Siftia Rusydi, Wasilatur Rahmah; Habsy, Bakhrudin All; Winingsih, Evi; Purwoko, Budi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to explore the meaning of life among children with cancer and to examine the role of community guidance and counseling in their meaning-making process. A qualitative approach with a phenomenological design was employed. The participants were two female children under 18 years old diagnosed with bone cancer who had undergone transtibial amputation. Data were collected through observation, unstructured interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing, with triangulation to ensure data trustworthiness. The findings reveal that both participants have discovered their meaning of life as reflected in Viktor Frankl’s three sources of values: creative, experiential, and attitudinal values. Creative values were expressed through drawing as a medium for emotional catharsis; experiential values were reflected in relational experiences and future aspirations shaped by their experiences as cancer patients; and attitudinal values were demonstrated through acceptance of their condition, resilience in undergoing treatment, and spiritual orientation. Community guidance and counseling played a significant role through group guidance, individual counseling, and psychoeducation and advocacy to enhance social support. These findings highlight that a community-based counseling approach contributes to strengthening the meaning of life and psychological well-being of children with cancer.